2021
DOI: 10.1016/j.landusepol.2020.105097
|View full text |Cite
|
Sign up to set email alerts
|

Off-farm employment and agricultural land use efficiency in China

Abstract: The non-agricultural employment transfer of the rural labor force has fundamentally changed the labor input in China in recent decades. A good understanding of how the off-farm employment of rural laborers affects agricultural land use in China is needed. We use the Driscoll and Kraay standard errors fixed effects model to investigate the relationship between rural laborers' off-farm employment and agricultural land use efficiency based on a panel data of 1,961 counties in China. We find that the distribution … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
47
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(47 citation statements)
references
References 49 publications
0
47
0
Order By: Relevance
“…The age of male or female farmers was not found to be significant in a study of Koirala et al [44]. Zhao et al [47] identified a robust U-shaped relationship between off-farm labor and agricultural land use efficiency, indicating that the relationship of non-agricultural income and agricultural land use efficiency was significantly positive after the turning point. When Jelsma et al [43] assessed the implementation of Good Agricultural Practices among different types of independent oil palm smallholders in Riau, Indonesia, they found that the wealthy farmers may not be able to implement better agricultural practices.…”
Section: Did Regression and Quantile Regression For Comprehensive Efficiencymentioning
confidence: 93%
“…The age of male or female farmers was not found to be significant in a study of Koirala et al [44]. Zhao et al [47] identified a robust U-shaped relationship between off-farm labor and agricultural land use efficiency, indicating that the relationship of non-agricultural income and agricultural land use efficiency was significantly positive after the turning point. When Jelsma et al [43] assessed the implementation of Good Agricultural Practices among different types of independent oil palm smallholders in Riau, Indonesia, they found that the wealthy farmers may not be able to implement better agricultural practices.…”
Section: Did Regression and Quantile Regression For Comprehensive Efficiencymentioning
confidence: 93%
“…[58]. However, it did not change the county-level agricultural land-use efficiency being lower than the national average efficiency level [59]. From the above, it can be seen that changes in the labor force structure have a certain impact on land fragmentation.…”
Section: The Direct Effect Of Land Fragmentation On Land-use Efficiencymentioning
confidence: 99%
“…Previous studies gradually enriched and improved the methods of measuring land-use efficiency. Using the entropy value method, data envelopment, and consequent frontier analysis, researchers have thoroughly studied the efficiency of urban, industrial, agricultural, and development zone land [22][23][24][25][26][27][28]. Furthermore, more attention has been paid to interaction mechanisms of land-use efficiency and systems such as urban spatial development, economic development, and urban ecology.…”
Section: Literature Review and Analytical Framework 21 Literature Reviewmentioning
confidence: 99%